Long-Term Conditions Questionnaire (LTCQ): initial validation survey among primary care patients and social care recipients in England. Issue 11 (3rd November 2017) - Potter, Caroline M; Batchelder, Laurie; A'Court, Christine; Geneen, Louise; Kelly, Laura; Fox, Diane; Baker, Matthew; Bostock, Jennifer; Coulter, Angela; Fitzpatrick, Ray; Forder, Julien E; Gibbons, Elizabeth; et al.
Abstract : Objective: The aim of this study was to validate a new generic patient-reported outcome measure, the Long-Term Conditions Questionnaire (LTCQ), among a diverse sample of health and social care users in England. Design: Cross-sectional validation survey. Data were collected through postal surveys (February 2016–January 2017). The sample included a healthcare cohort of patients recruited through primary care practices, and a social care cohort recruited through local government bodies that provide social care services. Participants: 1211 participants (24% confirmed social care recipients) took part in the study. Healthcare participants were recruited on the basis of having one of 11 specified long-term conditions (LTCs), and social care participants were recruited on the basis of receiving social care support for at least one LTC. The sample exhibited high multimorbidity, with 93% reporting two or more LTCs and 43% reporting a mental health condition. Outcome measures: The LTCQ's construct validity was tested with reference to the EQ-5D (5-level version), the Self-Efficacy for Managing Chronic Disease scale, an Activities of Daily Living scale and the Bayliss burden of morbidity scale. Results: Low levels of missing data for each item indicate acceptability of the LTCQ across the sample. The LTCQ exhibits high internal consistency (Cronbach's α=0.95) across the scale's 20 items and excellent test–retest reliability (intraclass correlation coefficient=0.94, 95% CI 0.93 to 0.95). Associations between the LTCQ and all reference measures were moderate to strong and in the expected directions, indicating convergent construct validity. Conclusions: This study provides evidence for the reliability and validity of the LTCQ, which has potential for use in both health and social care settings. The LTCQ could meet a need for holistic outcome measurement that goes beyond symptoms and physical function, complementing existing measures to capture fully what it means to live well with LTCs.